Law Enforcement of Criminal Forests and Land Fire in Kabupaten Indragiri Hilir, Province of Riau - Rizana (International Journal of Law and Public Policy, 2020)
Forest and land fires are not a rare phenomenon in Indonesia, especially in Riau Province. This research aims to explain the law enforcement of forest and land fire crimes in District of Indragiri Hilir, Riau Province. The method used in this research is socio-legal research. Based on Article 50 Paragraph (3) Letter d of Law Number 41 of 1999 it is stated that everyone is prohibited from burning forests. In line with that, based on Article 69 Paragraph (1) Letter h of Law Number 32 of 2009 it is stated that everyone is prohibited from clearing land by burning. However, in 2019 there will still be forest and land fires in District of Indragiri Hilir, Riau Province covering an area of approximately 827 hectares. The implementation of Law Number 41 of 1999 and Law Number 32 of 2009 concerning forest and land fires in District of Indragiri Hilir hasn’t run as expected. Burning forests and land is a crime. Law enforcement against forest and land fires in District of Indragiri Hilir based on Article 78 Paragraph (3) of Law Number 41 of 1999 states that anyone who intentionally burns a forest can be threatened with a maximum of 15 years imprisonment and a maximum fine IDR 5,000,000,000. Pursuant to Article 108 of Law Number 32 of 2009 it is also emphasized that every person who burns a land shall be sentenced to a minimum imprisonment of 3 years and a maximum of 10 years, and a fine of at least IDR 3,000,000,000 and a maximum of IDR 10,000,000,000.